2015
DOI: 10.1186/s40462-015-0030-0
|View full text |Cite
|
Sign up to set email alerts
|

Movement, resting, and attack behaviors of wild pumas are revealed by tri-axial accelerometer measurements

Abstract: BackgroundAccelerometers are useful tools for biologists seeking to gain a deeper understanding of the daily behavior of cryptic species. We describe how we used GPS and tri-axial accelerometer (sampling at 64 Hz) collars to monitor behaviors of free-ranging pumas (Puma concolor), which are difficult or impossible to observe in the wild. We attached collars to twelve pumas in the Santa Cruz Mountains, CA from 2010-2012. By implementing Random Forest models, we classified behaviors in wild pumas based on traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(132 citation statements)
references
References 34 publications
2
130
0
Order By: Relevance
“…These new devices have given us greater abilities to remotely measure foraging gains as well. Clusters of GPS locations can reveal the kill sites of large terrestrial predators (e.g., Knopff et al 2009), miniature video loggers can identify prey capture, and accelerometers can be used to identify prey capture in a host of species ranging from fish (Viviant et al 2014) to penguins (Watanabe et al 2014) to pumas (Wang et al 2015).…”
Section: Foraging Behaviormentioning
confidence: 99%
“…These new devices have given us greater abilities to remotely measure foraging gains as well. Clusters of GPS locations can reveal the kill sites of large terrestrial predators (e.g., Knopff et al 2009), miniature video loggers can identify prey capture, and accelerometers can be used to identify prey capture in a host of species ranging from fish (Viviant et al 2014) to penguins (Watanabe et al 2014) to pumas (Wang et al 2015).…”
Section: Foraging Behaviormentioning
confidence: 99%
“…This results in a potential maximum recording longevity in the order of minutes to days, unless sub-sampling techniques are used (Hammond, Springthorpe, Walsh, & Berg-Kirkpatrick, 2016). However, the few studies that have directly tested this possibility suggested that low recording frequencies have significantly reduced accuracy when using current classification methods (Broell et al, 2013;Pagano et al, 2017;Wang et al, 2015). An alternative method is to extend the sampling duration by reducing the sampling rate.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of methods can determine whether accelerometer data are reliably correlated with behaviors, some of which are being developed for general use Resheff et al, 2014;Sakamoto et al, 2009). In some cases where an independent captive study is not possible, animals may be observed in zoos or in the wild, or surrogate species may be used Grünewälder et al, 2012;Nathan et al, 2012;Wang et al, 2015). Additionally, we assessed the accuracy of our system using a cross-validation method, which generated a system that was robust to individual differences in behavior.…”
Section: Validation Techniquesmentioning
confidence: 99%